The pressure effects and vibrational properties of energetic material: Hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (α‐RDX). (11th March 2019) - Fan, Junyu; Su, Yan; Zheng, Zhaoyang; Zhang, Qingyu; Zhao, Jijun
Abstract: Hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) is a secondary high‐explosive material with thermal stability and high‐detonation velocity. It has been widely utilized for military and civilian purposes. Using systematic first‐principle calculations, we comprehensively explore structural, mechanical, electronic, and vibrational properties of α ‐RDX modulated by pressure loading. The evolutions of structure, elastic modulus, and band gap are examined. A near‐linear pressure response and strong anisotropy are shown preliminarily. Further, pressure response and strong anisotropy are exhibited by Raman spectra analysis under hydrostatic and uniaxial compressions. Calculated Raman spectrum is well in accordance with experimental data at ambient conditions. Under uniaxial compression, the anisotropic vibration properties of α ‐RDX in different lattice directions are presented. The discontinuity in b axis and red shift along c axis, which is related to the modification of the strength of noncovalent interactions, is highlighted. Our results exhibit the comprehensive pressure responses and anisotropy of α ‐RDX on the atomic level. Abstract : The pressure effects and vibrational properties of RDX are simulated under various loading conditions. The results indicate that the anomalous Raman shifts, such as the discontinuity in b axis and red shift along c axis, are strongly related to the orientation of nitro groups, thereby further revealing the importance of nitro groups in the modification of molecular configuration.